A wide band gap perovskite thin film, a preparation method and application thereof
Patent Information
- Application Number
- CN202611113920.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-27
- Publication Date
- 2026-10-23
- Estimated Expiration
- 2046-07-27
AI Technical Summary
此外,晶界富含深能级缺陷,不仅作为非辐射复合中心,还为卤素离子迁移提供了快速扩散通道,进一步加剧相分离,造成带隙偏移、开路电压(Voc)和填充因子(FF)下降,器件性能迅速衰减
(1)本发明开发了一种基于2-甲基丙烯酸酐交联的双功能策略,可同时实现原位交联晶界钝化,并调控卤化物相的均匀性,用于宽带隙钙钛矿太阳能电池。2-甲基丙烯酸酐能够抑制溴富集的优先成核,在溴组分含量较高的宽带隙钙钛矿结晶过程中促使碘组分和溴组分同步结晶使得卤素分布均一化,促进碘/溴同步共结晶,从源头上消除相分离。在热退火过程中,2-甲基丙烯酸酐在晶界处发生交联,在晶界处形成坚固的聚合物网络,有效钝化晶界缺陷、阻挡离子迁移,提升稳定性。同时在宽带隙钙钛矿吸光层上表面形成的2-甲基丙烯酸酐交联界面层进一步钝化表面缺陷,阻挡水分入侵,抑制操作应力引发的应变,提升宽带隙钙钛矿器件的效率和稳定性。
Smart Images

Figure CN122662565B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of perovskite photovoltaic device technology, specifically relating to a wide-bandgap perovskite thin film, its preparation method, and its application. Background Technology
[0002] To overcome the inherent Shockley-Quiethor limit (SQ) of single-junction photovoltaics, tandem solar cells have become a key research focus and a promising technological approach. Wide-bandgap perovskite solar cells, as the top absorber layer in high-efficiency tandem solar cells, directly impact the industrialization of tandem solar cells due to their efficiency and stability.
[0003] However, wide-bandgap perovskites face challenges related to photoinduced phase separation and ion migration, severely limiting device efficiency and long-term stability. The fundamental reason lies in the fact that the bromine component in the precursor preferentially crystallizes due to its low solubility, forming bromine-rich nuclei, followed by Io... - Gradual insertion leads to uneven halogen distribution during initial crystallization, which eventually intensifies phase separation due to halide ion migration under light or electric fields. Furthermore, grain boundaries are rich in deep-level defects, which not only act as non-radiative recombination centers but also provide rapid diffusion channels for halide ion migration, further exacerbating phase separation. This results in bandgap shift, a decrease in open-circuit voltage (Voc) and fill factor (FF), and a rapid degradation of device performance. Although the introduction of some traditional materials such as rubidium chloride, lead thiocyanate, and benzamide chloride into wide-bandgap perovskite precursor solutions has achieved some effect in suppressing phase separation, it still does not solve the problem of I... - and Br - The issue of simultaneous crystallization of components. Effectively suppressing phase separation fundamentally requires simultaneous crystallization. - and Br - The components crystallize while stabilizing the grain boundaries. Summary of the Invention
[0004] To address the problems mentioned in the background section, the present invention aims to provide a wide-bandgap perovskite thin film, its preparation method, and its applications. The present invention involves adding 2-methacrylic anhydride (MAH) to the wide-bandgap perovskite precursor solution, causing it to crosslink in situ during the annealing of the perovskite, forming a crosslinked polymer network at the grain boundaries. This passivates grain boundary defects and blocks ion migration pathways. Simultaneously, 2-methacrylic anhydride promotes the simultaneous crystallization of iodine and bromine components during the crystallization process of the wide-bandgap perovskite, promoting the homogenization of halogen distribution. The present invention suppresses the problem of halogen phase separation in wide-bandgap perovskites from the source.
[0005] To achieve the above objectives, the technical solution adopted by the present invention is as follows: On the one hand, the present invention provides a wide-bandgap perovskite thin film, the wide-bandgap perovskite thin film comprising a wide-bandgap perovskite light-absorbing layer and a cross-linking interface layer, the cross-linking interface layer being located above the wide-bandgap perovskite light-absorbing layer; The raw materials for the wide-bandgap perovskite light-absorbing layer include 2-methacrylic anhydride and a wide-bandgap perovskite precursor solution; the wide-bandgap perovskite component in the wide-bandgap perovskite light-absorbing layer is Cs. y MA v FA 1-y-v Pb(I x Br 1-x 3. The optical band gap is 1.70 eV ~ 1.85 eV, where y = 0.02 ~ 0.5, v = 0.1, and x = 0.5 ~ 0.74; The raw materials for the cross-linked interface layer include 2-methacrylic anhydride, ethylenediamine dihydroiodate, azobisisobutyronitrile, and isopropanol.
[0006] Further, the wide-bandgap perovskite precursor solution comprises cesium iodide (CsI), lead iodide (PbI2), lead bromide (PbBr2), methylamine hydrobromide (MABr), formamidinium hydroiodide (FAI), and a solvent; the concentration of the wide-bandgap perovskite precursor solution is 1.2 mol / L ~ 1.7 mol / L, wherein the concentration is expressed as Pb... 2+ Concentration calculation; The mass ratio of the 2-methacrylic anhydride to the volume of the wide-bandgap perovskite precursor solution is (2 mg ~ 6 mg): 1 mL; the ratio of the 2-methacrylic anhydride, ethylenediamine dihydroiodate, and isopropanol is (1 mg ~ 4 mg): (0.3 mg ~ 2 mg): 1 mL; the mass of the azobisisobutyronitrile is 1% ~ 3% of the mass of the 2-methacrylic anhydride. The thickness of the wide-bandgap perovskite light-absorbing layer is 300 nm ~ 1000 nm; The thickness of the cross-linked interface layer is 3 nm to 20 nm.
[0007] Further, the solvent is a mixture of N,N-dimethylformamide (DMF) and dimethyl sulfoxide (DMSO), wherein the volume ratio of N,N-dimethylformamide to dimethyl sulfoxide is (1 ~ 6):1.
[0008] Furthermore, the wide-bandgap perovskite in the wide-bandgap perovskite light-absorbing layer has a composition of Cs. 0.02 MA 0.1 FA 0.88 Pb(I 0.74 Br 0.26 )3, with an optical band gap of 1.70 eV.
[0009] Furthermore, the wide-bandgap perovskite in the wide-bandgap perovskite light-absorbing layer has a composition of Cs. 0.1 MA 0.1 FA0.8 Pb(I 0.74 Br 0.26 )3, with an optical band gap of 1.71 eV.
[0010] Furthermore, the wide-bandgap perovskite in the wide-bandgap perovskite light-absorbing layer has a composition of Cs. 0.5 MA 0.1 FA 0.4 Pb(I 0.74 Br 0.26 )3, with an optical band gap of 1.77 eV.
[0011] Furthermore, the wide-bandgap perovskite in the wide-bandgap perovskite light-absorbing layer has a composition of Cs. 0.1 MA 0.1 FA 0.8 Pb(I 0.5 Br 0.5 )3, with an optical band gap of 1.85 eV.
[0012] On the other hand, the present invention provides a method for preparing any of the above-described wide-bandgap perovskite thin films, comprising the following steps: (1) Add 2-methacrylic anhydride to a wide-bandgap perovskite precursor solution and mix evenly to obtain a mixed solution; spin-coat the mixed solution onto a substrate and perform solvent removal and annealing treatments successively to obtain a wide-bandgap perovskite light-absorbing layer with in-situ crosslinked polymer filling the grain boundaries on the substrate. (2) Dissolve 2-methacrylic anhydride, azobisisobutyronitrile, and ethylenediamine dihydroiodate in isopropanol to obtain a mixed solution; spin-coat the mixed solution onto the wide-bandgap perovskite light-absorbing layer and anneal it to obtain a cross-linked interface layer above the wide-bandgap perovskite light-absorbing layer. The wide-bandgap perovskite light-absorbing layer and the cross-linked interface layer above the wide-bandgap perovskite light-absorbing layer are the wide-bandgap perovskite film.
[0013] Furthermore, the method for removing the solvent in step (1) is to quickly remove the solvent by vacuum flash evaporation; The annealing temperature in step (1) is 90℃ ~ 150℃, and the annealing time is 15 min ~ 30 min; The annealing temperature in step (2) is 60℃ ~ 120℃; the annealing time is 3 min ~ 15 min.
[0014] On the other hand, the present invention provides an application of the wide-bandgap perovskite thin film described above or the wide-bandgap perovskite thin film prepared by any of the above preparation methods in wide-bandgap perovskite solar cells.
[0015] In another aspect, the present invention provides a wide-bandgap perovskite solar cell, which, from bottom to top, comprises a transparent conductive substrate, a hole transport layer, a self-assembled monolayer, a wide-bandgap perovskite light-absorbing layer, a cross-linked interface layer, an electron transport layer, and a metal electrode layer. The wide-bandgap perovskite light-absorbing layer and cross-linking interface layer are either wide-bandgap perovskite films as described above or wide-bandgap perovskite films prepared by any of the preparation methods described above.
[0016] Furthermore, the cross-linked interface layer acts as a barrier layer, blocking moisture intrusion and suppressing strain caused by operational stress.
[0017] Furthermore, the transparent conductive substrate is ITO conductive glass; The hole transport layer is NiO. x Where x = 1 ~ 2; the thickness of the hole transport layer is 10 nm ~ 50 nm; The self-assembled monolayer is (3,8-difluoroindole[2,3-a]carbazole-11,12-diyl)bis(propane-3,1-diyl)bis(phosphonic acid) (3BPIC-F); the thickness of the self-assembled monolayer is 1 nm ~ 10 nm. The thickness of the wide-bandgap perovskite light-absorbing layer is 300 nm ~ 1000 nm; The thickness of the cross-linked interface layer is 3 nm to 20 nm; The electron transport layer is [6,6]-phenyl-C 61 methyl butyrate (PC) 61 (BM); the thickness of the electron transport layer is 10 nm ~ 50 nm; The metal electrode layer is a silver electrode layer or a copper electrode layer; the thickness of the metal electrode layer is 100 nm to 150 nm.
[0018] Furthermore, the present invention provides a method for fabricating the aforementioned wide-bandgap perovskite solar cell, comprising the following steps: (1) The ITO conductive glass was ultrasonically cleaned in sequence with detergent, deionized water, acetone, isopropanol and ethanol, dried with nitrogen gas, and treated with ultraviolet ozone to obtain the pretreated ITO conductive glass. (2) NiO x An aqueous solution was spin-coated onto the pretreated ITO conductive glass and annealed to obtain a hole transport layer. (3) Spin-coating a solution of (3,8-difluoroindole[2,3-a]carbazole-11,12-diyl)bis(propane-3,1-diyl)bis(phosphonic acid) onto the hole transport layer and annealing it to obtain a self-assembled monolayer. (4) Add 2-methacrylic anhydride to the wide-bandgap perovskite precursor solution and mix evenly to obtain a mixed solution; spin-coat the mixed solution onto the self-assembled monolayer, quickly remove the solvent by vacuum flash evaporation, and anneal to obtain a wide-bandgap perovskite light-absorbing layer. (5) Dissolve 2-methacrylic anhydride, azobisisobutyronitrile (AIBN), and ethylenediamine dihydroiodate in isopropanol (IPA) to obtain a mixed solution; spin-coat the mixed solution onto the wide-bandgap perovskite light-absorbing layer and anneal to obtain a cross-linked interface layer; (6) [6,6]-phenyl-C 61 A chlorobenzene solution of methyl butyrate was spin-coated onto the cross-linked interface layer to obtain an electron transport layer. (7) A layer of silver or copper is deposited on the electron transport layer by vacuum evaporation to obtain a metal electrode layer.
[0019] Further, the ultrasonic cleaning frequency in step (1) is 20 kHz ~ 300 kHz, the ultrasonic cleaning power is 200 W ~ 800 W, the ultrasonic cleaning time is 10 min ~ 30 min; the ultraviolet ozone treatment time is 10 min ~ 30 min. The NiO mentioned in step (2) x The aqueous solution concentration is 10 mg / mL to 20 mg / mL; the spin coating speed is 3000 r / s to 5000 r / s, and the spin coating time is 20 s to 60 s; the annealing temperature is 120℃ to 160℃, and the annealing time is 10 min to 30 min. The concentration of the (3,8-difluoroindole[2,3-a]carbazole-11,12-diyl)bis(propane-3,1-diyl)bis(phosphonic acid) solution in step (3) is 0.2 mg / mL to 1 mg / mL; the solvent used in the (3,8-difluoroindole[2,3-a]carbazole-11,12-diyl)bis(propane-3,1-diyl)bis(phosphonic acid) solution is selected from ethanol, N,N-dimethylformamide (DMF), or a mixture of N,N-dimethylformamide (DMF) and isopropanol; the spin coating speed is 3000 r / s to 8000 r / s, and the spin coating time is 20 s to 60 s; the annealing temperature is 80℃ to 120℃, and the annealing time is 5 min to 20 min; In step (4), the spin coating speed is 3000 r / s ~ 8000 r / s, and the spin coating time is 20 s ~ 60 s; the vacuum pressure is 10 Pa ~ 100 Pa, and the vacuum time is 20 s ~ 60 s; the annealing temperature is 90℃ ~ 150℃, and the annealing time is 15 min ~ 30 min; In step (5), the spin coating speed is 3000 r / s ~ 8000 r / s, the spin coating time is 10 s ~ 50 s, the annealing temperature is 60℃ ~ 120℃, and the annealing time is 3 min ~ 15 min. The [6,6]-phenyl-C described in step (6) 61 The concentration of the chlorobenzene solution of methyl butyrate is 10 mg / mL to 30 mg / mL; the spin coating speed is 1000 r / s to 5000 r / s, and the spin coating time is 10 s to 50 s.
[0020] Compared with the prior art, the present invention has the following beneficial effects: (1) This invention develops a bifunctional strategy based on 2-methacrylic anhydride crosslinking, which can simultaneously achieve in-situ crosslinking grain boundary passivation and regulate the uniformity of halide phases for use in wide-bandgap perovskite solar cells. 2-methacrylic anhydride can suppress preferential nucleation of bromine enrichment, promote the synchronous crystallization of iodine and bromine components during the crystallization process of wide-bandgap perovskite with high bromine content, thereby homogenizing the halogen distribution and promoting synchronous co-crystallization of iodine / bromine, eliminating phase separation at the source. During thermal annealing, 2-methacrylic anhydride crosslinks at the grain boundaries, forming a robust polymer network that effectively passivates grain boundary defects, blocks ion migration, and improves stability. At the same time, the 2-methacrylic anhydride crosslinked interface layer formed on the upper surface of the wide-bandgap perovskite light-absorbing layer further passivates surface defects, blocks moisture intrusion, suppresses strain caused by operating stress, and improves the efficiency and stability of wide-bandgap perovskite devices.
[0021] (2) In terms of device performance, the device optimized based on 1.71 eV bandgap perovskite achieved a photoelectric conversion efficiency of 22.56%, an open-circuit voltage of 1.285 V, and a fill factor of 83.03%. The device optimized based on 1.85 eV bandgap perovskite achieved a photoelectric conversion efficiency of 18.87%, an open-circuit voltage of 1.366 V, and a fill factor of 83.92%. This provides a high-performance front cell for perovskite / organic solar tandem cells. Attached Figure Description
[0022] Figure 1The Fourier transform infrared spectra of the wide-bandgap perovskite film without 2-methacrylic anhydride, the unannealed wide-bandgap perovskite film with 2-methacrylic anhydride, and the annealed wide-bandgap perovskite film with 2-methacrylic anhydride are shown in this invention. Figure 2 This is the photoluminescence spectrum of the wide-bandgap perovskite thin film prepared in Example 1 of the present invention as a function of illumination time; Figure 3 This is the photoluminescence spectrum of the wide-bandgap perovskite thin film prepared in Comparative Example 1 of this invention as a function of illumination time; Figure 4 This is a comparison of the current-voltage curves of the wide-bandgap perovskite solar cells prepared in Example 1 and Comparative Example 1 of this invention. Figure 5 This is the photoluminescence spectrum of the wide-bandgap perovskite thin film prepared in Example 2 of the present invention as a function of illumination time; Figure 6 This is the photoluminescence spectrum of the wide-bandgap perovskite thin film prepared in Comparative Example 2 of this invention as a function of illumination time; Figure 7 This is the photoluminescence spectrum of the wide-bandgap perovskite thin film prepared in Example 3 of the present invention as a function of illumination time; Figure 8 This is the photoluminescence spectrum of the wide-bandgap perovskite thin film prepared in Comparative Example 3 of this invention as a function of illumination time; Figure 9 This is the current-voltage curve of the wide-bandgap perovskite solar cell prepared in Example 4 of the present invention. Detailed Implementation
[0023] To better understand the content of this invention, the following detailed description is provided in conjunction with specific implementation methods. However, the scope of protection of this invention is not limited to the following embodiments.
[0024] Preparation of wide-bandgap perovskite films without 2-methacrylic anhydride: (1) ITO conductive glass was ultrasonically cleaned sequentially with detergent, deionized water, acetone, isopropanol, and ethanol (the ultrasonic cleaning frequency was 80 kHz, the power was 800 W, and the time was 30 min). It was dried with nitrogen gas and treated with ultraviolet ozone for 30 min to obtain pretreated ITO conductive glass; (2) Wide-bandgap perovskite precursor solution was spin-coated onto the pretreated ITO conductive glass, the solvent was quickly removed by vacuum flash evaporation, and annealed to obtain wide-bandgap perovskite films without 2-methacrylic anhydride. The wide-bandgap perovskite component in the wide-bandgap perovskite films without 2-methacrylic anhydride is Cs. 0.1 MA 0.1 FA 0.8Pb(I 0.74 Br 0.26 3. The wide-bandgap perovskite precursor solution consists of cesium iodide, lead iodide, lead bromide, methylamine hydrobromide, formamidinium hydroiodide, and a solvent. The concentration of the wide-bandgap perovskite precursor solution is 1.5 mol / L, with the concentration expressed as Pb. 2+ Concentration calculation; the solvent is a mixture of N,N-dimethylformamide and dimethyl sulfoxide, with a volume ratio of 3:1; the spin coating speed is 3000 r / s, and the spin coating time is 30 s; the vacuum pressure is 100 Pa, and the vacuum time is 50 s; the annealing temperature is 100℃, and the annealing time is 15 min.
[0025] Preparation of unannealed wide-bandgap perovskite film with added 2-methacrylic anhydride: (1) ITO conductive glass was ultrasonically cleaned sequentially with detergent, deionized water, acetone, isopropanol and ethanol (the ultrasonic cleaning frequency was 80 kHz, the power was 800 W and the time was 30 min), dried with nitrogen gas, and treated with ultraviolet ozone for 30 min to obtain pretreated ITO conductive glass; (2) 2-methacrylic anhydride was added to the wide-bandgap perovskite precursor solution and mixed evenly to obtain a mixed solution; the mixed solution was spin-coated onto the pretreated ITO conductive glass, and the solvent was quickly removed by vacuum flash evaporation to obtain unannealed wide-bandgap perovskite film with added 2-methacrylic anhydride. The wide-bandgap perovskite component in the unannealed wide-bandgap perovskite film with added 2-methacrylic anhydride is Cs 0.1 MA 0.1 FA 0.8 Pb(I 0.74 Br 0.26 3. The mass ratio of 2-methacrylic anhydride to the volume of the wide-bandgap perovskite precursor solution is 3 mg: 1 mL; the wide-bandgap perovskite precursor solution consists of cesium iodide, lead iodide, lead bromide, methylamine hydrobromide, formamidinium hydroiodide, and solvent; the concentration of the wide-bandgap perovskite precursor solution is 1.5 mol / L, with the concentration expressed as Pb. 2+ Concentration calculation; the solvent is a mixture of N,N-dimethylformamide and dimethyl sulfoxide, with a volume ratio of 3:1; the spin coating speed is 3000 r / s, the spin coating time is 30 s; the vacuum pressure is 100 Pa, and the vacuum time is 50 s.
[0026] Preparation of annealed wide-bandgap perovskite film with added 2-methacrylic anhydride: (1) ITO conductive glass was ultrasonically cleaned sequentially with detergent, deionized water, acetone, isopropanol and ethanol (the ultrasonic cleaning frequency was 80 kHz, the power was 800 W and the time was 30 min), dried with nitrogen gas, and treated with ultraviolet ozone for 30 min to obtain pretreated ITO conductive glass; (2) 2-methacrylic anhydride was added to the wide-bandgap perovskite precursor solution and mixed evenly to obtain a mixed solution; the mixed solution was spin-coated onto the pretreated ITO conductive glass, the solvent was quickly removed by vacuum flash evaporation, and annealed to obtain annealed wide-bandgap perovskite film with added 2-methacrylic anhydride. The wide-bandgap perovskite component in the annealed wide-bandgap perovskite film with added 2-methacrylic anhydride is Cs 0.1 MA 0.1 FA 0.8 Pb(I 0.74 Br 0.26 3. The mass ratio of 2-methacrylic anhydride to the volume of the wide-bandgap perovskite precursor solution is 3 mg: 1 mL; the wide-bandgap perovskite precursor solution consists of cesium iodide, lead iodide, lead bromide, methylamine hydrobromide, formamidinium hydroiodide, and solvent; the concentration of the wide-bandgap perovskite precursor solution is 1.5 mol / L, with the concentration expressed as Pb. 2+ Concentration calculation; the solvent is a mixture of N,N-dimethylformamide and dimethyl sulfoxide, with a volume ratio of 3:1; the spin coating speed is 3000 r / s, and the spin coating time is 30 s; the vacuum pressure is 100 Pa, and the vacuum time is 50 s; the annealing temperature is 100℃, and the annealing time is 15 min.
[0027] Fourier transform infrared spectroscopy was performed on wide-bandgap perovskite films without 2-methacrylic anhydride, unannealed wide-bandgap perovskite films with 2-methacrylic anhydride, and annealed wide-bandgap perovskite films with 2-methacrylic anhydride. The results are as follows: Figure 1 As shown. From Figure 1 As can be seen, the spectrum of the wide-bandgap perovskite film without the addition of 2-methacrylic anhydride did not reach a wavenumber of 1650 cm⁻¹. -1 The C=C tensile vibration peak at [location missing]; 1650 cm⁻¹ in unannealed wide-bandgap perovskite films with added 2-methacrylic anhydride. -1 The C=C tensile vibration peak at [location missing]; the original 1650 cm⁻¹ peak in the annealed wide-bandgap perovskite film after the addition of 2-methacrylic anhydride. -1 The C=C tensile vibration peak disappeared, indicating that the in-situ crosslinking of 2-methacrylic anhydride successfully occurred during the wide-bandgap perovskite crystallization process.
[0028] Example 1 Wide-bandgap perovskite thin film: This film comprises a wide-bandgap perovskite absorbing layer and a cross-linked interface layer, with the cross-linked interface layer located above the wide-bandgap perovskite absorbing layer. The thickness of the wide-bandgap perovskite absorbing layer is 500 nm, and the thickness of the cross-linked interface layer is 5 nm. The raw materials for the wide-bandgap perovskite absorbing layer include 2-methacrylic anhydride and a wide-bandgap perovskite precursor solution; the wide-bandgap perovskite component in the wide-bandgap perovskite absorbing layer is Cs. 0.1 MA 0.1 FA 0.8 Pb(I 0.74 Br 0.26 3. The optical band gap is 1.71 eV; the mass ratio of 2-methacrylic anhydride to the volume of the wide-bandgap perovskite precursor solution is 3 mg: 1 mL. The wide-bandgap perovskite precursor solution consists of cesium iodide, lead iodide, lead bromide, methylamine hydrobromide, formamidinium hydroiodide, and solvent. The concentration of the wide-bandgap perovskite precursor solution is 1.5 mol / L, with the concentration expressed as Pb. 2+ Concentration calculation; the solvent is a mixture of N,N-dimethylformamide and dimethyl sulfoxide, with a volume ratio of 3:1. The raw materials for the crosslinking interface layer include 2-methacrylic anhydride, ethylenediamine dihydroiodate, azobisisobutyronitrile, and isopropanol; the ratio of 2-methacrylic anhydride, ethylenediamine dihydroiodate, and isopropanol is 3 mg:1 mg:1 mL, and the mass of azobisisobutyronitrile is 1% of the mass of 2-methacrylic anhydride.
[0029] Preparation of wide-bandgap perovskite thin films: (1) ITO conductive glass was ultrasonically cleaned sequentially with detergent, deionized water, acetone, isopropanol and ethanol (the ultrasonic cleaning frequency was 80 kHz, the power was 800 W and the time was 30 min), dried with nitrogen gas, and treated with ultraviolet ozone for 30 min to obtain pretreated ITO conductive glass; (2) 2-methacrylic anhydride was added to the wide-bandgap perovskite precursor solution and mixed evenly to obtain a mixed solution; the mixed solution was spin-coated onto the pretreated ITO conductive glass, the solvent was quickly removed by vacuum flash evaporation, and annealed to obtain a wide-bandgap perovskite light-absorbing layer; the spin-coating speed was 3000 r / s and the spin-coating time was 30 s; the vacuum pressure was 100 Pa and the vacuum time was 50 s; the annealing temperature was 100℃ and the annealing time was 15 s. min; (3) Dissolve 2-methacrylic anhydride, azobisisobutyronitrile, and ethylenediamine dihydroiodate in isopropanol to obtain a mixed solution; spin-coat the mixed solution onto a wide-bandgap perovskite light-absorbing layer and anneal it to obtain a cross-linked interface layer above the wide-bandgap perovskite light-absorbing layer. The wide-bandgap perovskite light-absorbing layer and the cross-linked interface layer above the wide-bandgap perovskite light-absorbing layer are the wide-bandgap perovskite film; the spin-coating speed is 5000 r / s, the spin-coating time is 30 s, the annealing temperature is 100℃, and the annealing time is 5 min.
[0030] Wide-bandgap perovskite solar cells: From bottom to top, they consist of a transparent conductive substrate, a hole transport layer, a self-assembled monolayer, a wide-bandgap perovskite light-absorbing layer, a cross-linking interface layer, an electron transport layer, and a metal electrode layer. The transparent conductive substrate is ITO conductive glass; the hole transport layer is NiO. x Where x = 1 ~ 2, the hole transport layer has a thickness of 10 nm; the self-assembled monolayer is (3,8-difluoroindole[2,3-a]carbazole-11,12-diyl)bis(propane-3,1-diyl)bis(phosphonic acid), and the self-assembled monolayer has a thickness of 2 nm; the wide-bandgap perovskite light-absorbing layer and the cross-linking interface layer are the above-mentioned wide-bandgap perovskite films; the thickness of the wide-bandgap perovskite light-absorbing layer is 500 nm; the thickness of the cross-linking interface layer is 5 nm; the electron transport layer is [6,6]-phenyl-C 61 - Methyl butyrate, with an electron transport layer thickness of 30 nm; the metal electrode layer is a silver electrode layer with a thickness of 100 nm.
[0031] A method for fabricating wide-bandgap perovskite solar cells includes the following steps: (1) The ITO conductive glass was ultrasonically cleaned in sequence with detergent, deionized water, acetone, isopropanol and ethanol (the ultrasonic cleaning frequency was 80 kHz, the power was 800 W and the time was 30 min). It was dried with nitrogen gas and treated with ultraviolet ozone for 30 min to obtain the pretreated ITO conductive glass. (2) NiO x An aqueous solution of NiO was spin-coated onto pretreated ITO conductive glass and annealed to obtain a hole transport layer; wherein NiO x The aqueous solution concentration was 10 mg / mL; the spin coating speed was 3000 r / s, the spin coating time was 30 s; the annealing temperature was 150℃, and the annealing time was 15 min. (3) A solution of (3,8-difluoroindole[2,3-a]carbazole-11,12-diyl)bis(propane-3,1-diyl)bis(phosphonic acid) was spin-coated onto a hole transport layer and annealed to obtain a self-assembled monolayer; wherein the concentration of the (3,8-difluoroindole[2,3-a]carbazole-11,12-diyl)bis(propane-3,1-diyl)bis(phosphonic acid) solution was 0.8 mg / mL; the solvent used in the (3,8-difluoroindole[2,3-a]carbazole-11,12-diyl)bis(propane-3,1-diyl)bis(phosphonic acid) solution was selected from ethanol; the spin-coating speed was 8000 r / s, the spin-coating time was 30 s; the annealing temperature was 100℃, and the annealing time was 10 min; (4) Add 2-methacrylic anhydride to the wide-bandgap perovskite precursor solution and mix evenly to obtain a mixed solution; spin-coat the mixed solution onto a self-assembled monolayer, quickly remove the solvent by vacuum flash evaporation, and anneal to obtain a wide-bandgap perovskite light-absorbing layer; wherein the spin-coating speed is 3000 r / s, the spin-coating time is 30 s; the vacuum pressure is 100 Pa, the vacuum time is 50 s; the annealing temperature is 100℃, and the annealing time is 15 min; (5) Dissolve 2-methacrylic anhydride, azobisisobutyronitrile, and ethylenediamine dihydroiodate in isopropanol to obtain a mixed solution; spin-coat the mixed solution onto a wide-bandgap perovskite light-absorbing layer and anneal to obtain a cross-linked interface layer; wherein the spin-coating speed is 5000 r / s, the spin-coating time is 30 s, the annealing temperature is 100℃, and the annealing time is 5 min; (6) [6,6]-phenyl-C 61 A chlorobenzene solution of methyl butyrate was spin-coated onto the cross-linked interface layer to obtain an electron transport layer; wherein [6,6]-phenyl-C 61 The concentration of the chlorobenzene solution of methyl butyrate was 20 mg / mL; the spin coating speed was 1200 r / s, and the spin coating time was 30 s; (7) A layer of silver is deposited on the electron transport layer by vacuum evaporation to obtain a metal electrode layer.
[0032] Comparative Example 1 Wide-bandgap perovskite thin films: their raw materials include wide-bandgap perovskite precursor solutions; the wide-bandgap perovskite component in the wide-bandgap perovskite thin films is Cs. 0.1 MA 0.1 FA 0.8 Pb(I 0.74 Br 0.26 3. The optical bandgap is 1.71 eV. The thickness of the wide bandgap perovskite film is 500 nm. The wide bandgap perovskite precursor solution consists of cesium iodide, lead iodide, lead bromide, methylamine hydrobromide, formamidinium hydroiodide, and solvent. The concentration of the wide bandgap perovskite precursor solution is 1.5 mol / L, with the concentration expressed as Pb. 2+ Concentration calculation; the solvent is a mixture of N,N-dimethylformamide and dimethyl sulfoxide, with a volume ratio of 3:1.
[0033] Preparation of wide-bandgap perovskite thin films: (1) ITO conductive glass was ultrasonically cleaned sequentially with detergent, deionized water, acetone, isopropanol and ethanol (the ultrasonic cleaning frequency was 80 kHz, the power was 800 W and the time was 30 min), dried with nitrogen gas, and treated with ultraviolet ozone for 30 min to obtain pretreated ITO conductive glass; (2) Wide-bandgap perovskite precursor solution was spin-coated onto the pretreated ITO conductive glass, the solvent was quickly removed by vacuum flash evaporation, and annealed to obtain wide-bandgap perovskite thin films; the spin-coating speed was 3000 r / s and the spin-coating time was 30 s; the vacuum pressure was 100 Pa and the vacuum time was 50 s; the annealing temperature was 100℃ and the annealing time was 15 min.
[0034] Wide-bandgap perovskite solar cells: From bottom to top, they consist of a transparent conductive substrate, a hole transport layer, a self-assembled monolayer, a wide-bandgap perovskite light-absorbing layer, an electron transport layer, and a metal electrode layer. The transparent conductive substrate is ITO conductive glass; the hole transport layer is NiO. x Where x = 1 ~ 2, the hole transport layer has a thickness of 10 nm; the self-assembled monolayer is (3,8-difluoroindole[2,3-a]carbazole-11,12-diyl)bis(propane-3,1-diyl)bis(phosphonic acid), and the self-assembled monolayer has a thickness of 2 nm; the wide-bandgap perovskite absorber layer is the above-mentioned wide-bandgap perovskite film, and the thickness of the wide-bandgap perovskite absorber layer is 500 nm; the electron transport layer is [6,6]-phenyl-C 61- Methyl butyrate, with an electron transport layer thickness of 30 nm; the metal electrode layer is a silver electrode layer with a thickness of 100 nm.
[0035] The fabrication method of wide-bandgap perovskite solar cells includes the following steps: (1) The ITO conductive glass was ultrasonically cleaned in sequence with detergent, deionized water, acetone, isopropanol and ethanol (the ultrasonic cleaning frequency was 80 kHz, the power was 800 W and the time was 30 min). It was dried with nitrogen gas and treated with ultraviolet ozone for 30 min to obtain the pretreated ITO conductive glass. (2) NiO x An aqueous solution of NiO was spin-coated onto pretreated ITO conductive glass and annealed to obtain a hole transport layer; wherein NiO x The aqueous solution concentration was 10 mg / mL; the spin coating speed was 3000 r / s, the spin coating time was 30 s; the annealing temperature was 150℃, and the annealing time was 15 min. (3) A solution of (3,8-difluoroindole[2,3-a]carbazole-11,12-diyl)bis(propane-3,1-diyl)bis(phosphonic acid) was spin-coated onto a hole transport layer and annealed to obtain a self-assembled monolayer; wherein the concentration of the (3,8-difluoroindole[2,3-a]carbazole-11,12-diyl)bis(propane-3,1-diyl)bis(phosphonic acid) solution was 0.8 mg / mL; the solvent used in the (3,8-difluoroindole[2,3-a]carbazole-11,12-diyl)bis(propane-3,1-diyl)bis(phosphonic acid) solution was selected from ethanol; the spin-coating speed was 8000 r / s, the spin-coating time was 30 s; the annealing temperature was 100℃, and the annealing time was 10 min; (4) Spin-coating the wide-bandgap perovskite precursor solution onto a self-assembled monolayer, rapidly removing the solvent by vacuum flash evaporation, and annealing to obtain a wide-bandgap perovskite light-absorbing layer; wherein the spin-coating speed is 3000 r / s, the spin-coating time is 30s; the vacuum pressure is 100 Pa, the vacuum time is 50 s; the annealing temperature is 100℃, and the annealing time is 15min. (5) [6,6]-phenyl-C 61 A chlorobenzene solution of methyl butyrate was spin-coated onto the cross-linked interface layer to obtain an electron transport layer; wherein [6,6]-phenyl-C 61 The concentration of the chlorobenzene solution of methyl butyrate was 20 mg / mL; the spin coating speed was 1200 r / s, and the spin coating time was 30 s; (6) A layer of silver is deposited on the electron transport layer by vacuum evaporation to obtain a metal electrode layer.
[0036] Steady-state photoluminescence spectroscopy was performed on the wide-bandgap perovskite thin film prepared in Example 1, and the results are as follows: Figure 2 As shown. From Figure 2 The peak shift of the photoluminescence spectrum of the medium-wide bandgap perovskite film with illumination time shows that after 31 min of illumination, the peak position of the photoluminescence spectrum remained essentially unchanged compared to the initial position, indicating that phase separation was significantly suppressed in this embodiment. This suppression of phase separation can be attributed to: 1) the simultaneous crystallization of iodine and bromine components during the crystallization process of 2-methacrylic anhydride. - and Br - 1) Uniform distribution, which inhibits phase separation at the source; 2) 2-Methacrylic anhydride crosslinks in situ during the annealing and crystallization of wide-bandgap perovskite to form a polymer crosslink network and fill the grain boundaries, blocking the path of ion migration; 3) The 2-methacrylic anhydride crosslinked interface layer formed on the top of the wide-bandgap perovskite film can block moisture intrusion and suppress the strain of photothermal and other operational stresses, suppressing lattice distortion, thus further inhibiting phase separation.
[0037] Steady-state photoluminescence spectroscopy was performed on the wide-bandgap perovskite thin film prepared in Comparative Example 1, and the results are as follows: Figure 3 As shown. From Figure 3 The change in peak shift of the photoluminescence spectrum of the medium-bandgap perovskite thin film with illumination time shows that after 31 min of illumination, the peak position of the photoluminescence spectrum red-shifted by 20 nm compared with the initial value. This indicates that the film in this comparative example can undergo rapid phase separation under illumination, which seriously affects its long-term stability during operation.
[0038] Current-voltage curves were tested on the wide-bandgap perovskite solar cells prepared in Example 1 and Comparative Example 1, and the results are as follows: Figure 4 As shown. From Figure 4 As can be seen from the data, the wide-bandgap perovskite solar cell prepared in Example 1 has an effective active layer area of 0.0733 cm² on AM1.5. 2 Under these conditions, the short-circuit current density is 21.14 mA cm⁻¹. -2 With an open-circuit voltage of 1.285 V and a fill factor of 83.03%, a photoelectric conversion efficiency as high as 22.56% was achieved. The wide-bandgap perovskite solar cell prepared in Comparative Example 1, with an effective active layer area of 0.0733 cm², was also observed at AM 1.5. 2 Under these conditions, the short-circuit current density is 20.59 mA cm⁻¹. -2 The open-circuit voltage is 1.259 V, the fill factor is 81.70%, and the photoelectric conversion efficiency is 20.66%.
[0039] Example 2 The difference between this embodiment and Embodiment 1 is that the wide-bandgap perovskite in this embodiment is composed of Cs. 0.02 MA 0.1 FA 0.88 Pb(I 0.74 Br 0.26 )3, with an optical band gap of 1.70 eV.
[0040] Comparative Example 2 The difference between this comparative example and Comparative Example 1 is that the wide-bandgap perovskite film has a Cs composition. 0.02 MA 0.1 FA 0.88 Pb(I 0.74 Br 0.26 )3, with an optical band gap of 1.70 eV.
[0041] Steady-state photoluminescence spectroscopy was performed on the wide-bandgap perovskite thin film prepared in Example 2, and the results are as follows: Figure 5 As shown. From Figure 5 The change in peak shift of the photoluminescence spectrum of the medium-wide bandgap perovskite film with illumination time shows that after 30 min of illumination, the peak position of the photoluminescence spectrum basically did not shift, indicating that the photoinduced phase separation of the 1.70 eV wide bandgap perovskite was effectively suppressed.
[0042] Steady-state photoluminescence spectroscopy was performed on the wide-bandgap perovskite thin film prepared in Comparative Example 2, and the results are as follows: Figure 6 As shown. From Figure 6 The change in peak shift of the photoluminescence spectrum of the medium-wide bandgap perovskite thin film with illumination time shows that after 30 min of illumination, the peak of the photoluminescence spectrum red-shifted by 30 nm, indicating a serious problem of photoinduced phase separation.
[0043] Example 3 The difference between this embodiment and Embodiment 1 is that the wide-bandgap perovskite in this embodiment is composed of Cs. 0.5 MA 0.1 FA 0.4 Pb(I 0.74 Br 0.26 )3, with an optical band gap of 1.77 eV.
[0044] Comparative Example 3 The difference between this comparative example and Example 1 is that the wide-bandgap perovskite film has a Cs composition. 0.5 MA 0.1 FA 0.4 Pb(I 0.74 Br 0.26 )3, with an optical band gap of 1.77 eV.
[0045] Steady-state photoluminescence spectroscopy was performed on the wide-bandgap perovskite thin film prepared in Example 3, and the results are as follows: Figure 7 As shown. From Figure 7 The change in peak shift of the photoluminescence spectrum of the medium-wide bandgap perovskite film with illumination time shows that after 30 min of illumination, the peak of the photoluminescence spectrum basically did not shift, indicating that the photo-induced phase separation of the 1.77 eV wide bandgap perovskite was effectively suppressed.
[0046] Steady-state photoluminescence spectroscopy was performed on the wide-bandgap perovskite thin film prepared in Comparative Example 3, and the results are as follows: Figure 8 As shown. From Figure 8 The change in peak shift of the photoluminescence spectrum of the medium-wide bandgap perovskite thin film with illumination time shows that after 30 min of illumination, the peak of the photoluminescence spectrum red-shifted by 35 nm. With the increase of Cs content, the widening of the bandgap and the photoinduced phase separation problem become more and more serious.
[0047] Example 4 The difference between this embodiment and Embodiment 1 is that the wide-bandgap perovskite in this embodiment is composed of Cs. 0.1 MA 0.1 FA 0.8 Pb(I 0.5 Br 0.5 )3, with an optical band gap of 1.85 eV.
[0048] The wide-bandgap perovskite solar cell prepared in Example 4 was subjected to current-voltage curve testing, and the results are as follows: Figure 9 As shown. From Figure 9 As can be seen from the data, the wide-bandgap perovskite solar cell prepared in Example 4 has an effective active layer area of 0.0733 cm² at AM 1.5. 2 Under these conditions, the short-circuit current density is 16.52 mA cm⁻¹. -2 With an open-circuit voltage of 1.366 V and a fill factor of 83.92%, a photoelectric conversion efficiency of up to 18.87% was achieved. This provides a high-performance front cell for perovskite / organic solar tandem cells.
[0049] The above description is only a specific embodiment of the present invention and not all embodiments. Any equivalent modifications made by those skilled in the art to the technical solutions of the present invention by reading the present invention specification shall be covered by the claims of the present invention.
Claims
1. A wide-bandgap perovskite thin film, characterized in that, The wide-bandgap perovskite film includes a wide-bandgap perovskite light-absorbing layer and a cross-linking interface layer, wherein the cross-linking interface layer is located above the wide-bandgap perovskite light-absorbing layer. The raw materials for the wide-bandgap perovskite light-absorbing layer include 2-methacrylic anhydride and a wide-bandgap perovskite precursor solution; the wide-bandgap perovskite component in the wide-bandgap perovskite light-absorbing layer is Cs. y MA v FA 1-y-v Pb(I x Br 1-x 3. The optical band gap is 1.70 eV ~ 1.85 eV, where y = 0.02 ~ 0.5, v = 0.1, and x = 0.5 ~ 0.74; The raw materials for the cross-linked interface layer include 2-methacrylic anhydride, ethylenediamine dihydroiodate, azobisisobutyronitrile, and isopropanol.
2. The wide-bandgap perovskite thin film according to claim 1, characterized in that, The wide-bandgap perovskite precursor solution comprises cesium iodide, lead iodide, lead bromide, methylamine hydrobromide, formamidinium hydroiodide, and a solvent; the concentration of the wide-bandgap perovskite precursor solution is 1.2 mol / L ~ 1.7 mol / L, wherein the concentration is expressed as Pb. 2+ Concentration calculation; The mass ratio of the 2-methacrylic anhydride to the volume ratio of the wide-bandgap perovskite precursor solution is (2 mg ~ 6 mg): 1 mL; The ratio of 2-methacrylic anhydride, ethylenediamine dihydroiodate, and isopropanol is (1 mg ~ 4 mg): (0.3 mg ~ 2 mg): 1 mL; the mass of the azobisisobutyronitrile is 1% ~ 3% of the mass of 2-methacrylic anhydride. The thickness of the wide-bandgap perovskite light-absorbing layer is 300 nm ~ 1000 nm; The thickness of the cross-linked interface layer is 3 nm to 20 nm.
3. The wide-bandgap perovskite thin film according to claim 2, characterized in that, The solvent is a mixture of N,N-dimethylformamide and dimethyl sulfoxide, wherein the volume ratio of N,N-dimethylformamide to dimethyl sulfoxide is (1 ~ 6):
1.
4. The method for preparing a wide-bandgap perovskite thin film according to any one of claims 1-3, characterized in that, Includes the following steps: (1) Add 2-methacrylic anhydride to a wide-bandgap perovskite precursor solution and mix evenly to obtain a mixed solution; spin-coat the mixed solution onto a substrate, and perform solvent removal and annealing treatments successively to obtain a wide-bandgap perovskite light-absorbing layer on the substrate. (2) Dissolve 2-methacrylic anhydride, azobisisobutyronitrile, and ethylenediamine dihydroiodate in isopropanol to obtain a mixed solution; spin-coat the mixed solution onto the wide-bandgap perovskite light-absorbing layer and anneal it to obtain a cross-linked interface layer above the wide-bandgap perovskite light-absorbing layer. The wide-bandgap perovskite light-absorbing layer and the cross-linked interface layer above the wide-bandgap perovskite light-absorbing layer together constitute a wide-bandgap perovskite film.
5. The preparation method according to claim 4, characterized in that, The method for removing the solvent in step (1) is to quickly remove the solvent by vacuum flash evaporation; The annealing temperature in step (1) is 90℃ ~ 150℃, and the annealing time is 15 min ~ 30 min; The annealing temperature in step (2) is 60℃ ~ 120℃; the annealing time is 3 min ~ 15 min.
6. The application of the wide-bandgap perovskite thin film according to any one of claims 1-3 or the wide-bandgap perovskite thin film prepared by the preparation method according to any one of claims 4-5 in wide-bandgap perovskite solar cells.
7. A wide-bandgap perovskite solar cell, characterized in that, From bottom to top, it includes a transparent conductive substrate, a hole transport layer, a self-assembled monolayer, a wide-bandgap perovskite light-absorbing layer, a cross-linked interface layer, an electron transport layer, and a metal electrode layer. The wide-bandgap perovskite light-absorbing layer and cross-linking interface layer are wide-bandgap perovskite films according to any one of claims 1-3 or wide-bandgap perovskite films prepared by any one of claims 4-5.
8. The wide-bandgap perovskite solar cell according to claim 7, characterized in that, The transparent conductive substrate is ITO conductive glass; The hole transport layer is NiO. x , where x = 1 ~ 2; the thickness of the hole transport layer is 10 nm ~ 50 nm; The self-assembled monolayer is (3,8-difluoroindole[2,3-a]carbazole-11,12-diyl)bis(propane-3,1-diyl)bis(phosphonic acid); the thickness of the self-assembled monolayer is 1 nm ~ 10 nm. The thickness of the wide-bandgap perovskite light-absorbing layer is 300 nm ~ 1000 nm; The thickness of the cross-linked interface layer is 3 nm to 20 nm; The electron transport layer is [6,6]-phenyl-C 61 methyl butyrate; the thickness of the electron transport layer is 10 nm ~ 50 nm; The metal electrode layer is a silver electrode layer or a copper electrode layer; the thickness of the metal electrode layer is 100 nm to 150 nm.
9. The method for preparing the wide-bandgap perovskite solar cell according to claim 8, characterized in that, Includes the following steps: (1) The ITO conductive glass was ultrasonically cleaned in sequence with detergent, deionized water, acetone, isopropanol and ethanol, dried with nitrogen gas, and treated with ultraviolet ozone to obtain the pretreated ITO conductive glass. (2) NiO x An aqueous solution was spin-coated onto the pretreated ITO conductive glass and annealed to obtain a hole transport layer. (3) Spin-coating a solution of (3,8-difluoroindole[2,3-a]carbazole-11,12-diyl)bis(propane-3,1-diyl)bis(phosphonic acid) onto the hole transport layer and annealing it to obtain a self-assembled monolayer. (4) Add 2-methacrylic anhydride to the wide-bandgap perovskite precursor solution and mix evenly to obtain a mixed solution; spin-coat the mixed solution onto the self-assembled monolayer, quickly remove the solvent by vacuum flash evaporation, and anneal to obtain a wide-bandgap perovskite light-absorbing layer. (5) Dissolve 2-methacrylic anhydride, azobisisobutyronitrile, and ethylenediamine dihydroiodate in isopropanol to obtain a mixed solution; spin-coat the mixed solution onto the wide-bandgap perovskite light-absorbing layer and anneal to obtain a cross-linked interface layer; (6) [6,6]-phenyl-C 61 A chlorobenzene solution of methyl butyrate was spin-coated onto the cross-linked interface layer to obtain an electron transport layer. (7) A layer of silver or copper is deposited on the electron transport layer by vacuum evaporation to obtain a metal electrode layer.
10. The preparation method according to claim 9, characterized in that, The ultrasonic cleaning frequency in step (1) is 20kHz ~ 300kHz, the ultrasonic cleaning power is 200W ~ 800W, and the ultrasonic cleaning time is 10min ~ 30min; the ultraviolet ozone treatment time is 10min ~ 30min. The NiO mentioned in step (2) x The aqueous solution concentration is 10 mg / mL to 20 mg / mL; the spin coating speed is 3000 r / s to 5000 r / s, and the spin coating time is 20 s to 60 s; the annealing temperature is 120℃ to 160℃, and the annealing time is 10 min to 30 min. The concentration of the (3,8-difluoroindole[2,3-a]carbazole-11,12-diyl)bis(propane-3,1-diyl)bis(phosphonic acid) solution in step (3) is 0.2 mg / mL to 1 mg / mL; the solvent used in the (3,8-difluoroindole[2,3-a]carbazole-11,12-diyl)bis(propane-3,1-diyl)bis(phosphonic acid) solution is selected from ethanol, N,N-dimethylformamide, or a mixture of N,N-dimethylformamide and isopropanol; the spin coating speed is 3000 r / s to 8000 r / s, and the spin coating time is 20 s to 60 s; the annealing temperature is 80℃ to 120℃, and the annealing time is 5 min to 20 min; In step (4), the spin coating speed is 3000 r / s ~ 8000 r / s, the spin coating time is 20 s ~ 60 s; the vacuum pressure is 10 Pa ~ 100 Pa, the vacuum time is 20 s ~ 60 s; the annealing temperature is 90℃ ~ 150℃, and the annealing time is 15 min ~ 30 min; In step (5), the spin coating speed is 3000 r / s ~ 8000 r / s, the spin coating time is 10 s ~ 50 s, the annealing temperature is 60℃ ~ 120℃, and the annealing time is 3 min ~ 15 min. The [6,6]-phenyl-C described in step (6) 61 The concentration of the chlorobenzene solution of methyl butyrate is 10 mg / mL to 30 mg / mL; the spin coating speed is 1000 r / s to 5000 r / s, and the spin coating time is 10 s to 50 s.
Citation Information
Patent Citations
Electroactive perovskite hydrogel suitable for electrical stimulation bone regeneration as well as preparation and application of electroactive perovskite hydrogel
CN114539559A
Method for manufacturing patterned film substrate
CN118973347A